Coastal recirculation potential affecting air pollutants in Portugal: The role of circulation weather types. (June 2016) - Russo, Ana; Gouveia, Célia; Levy, Ilan; Dayan, Uri; Jerez, Sonia; Mendes, Manuel; Trigo, Ricardo
Abstract: Coastal zones are under increasing development and experience air pollution episodes regularly. These episodes are often related to peaks in local emissions from industry or transportation, but can also be associated with regional transport from neighbour urban areas influenced by land-sea breeze recirculation. This study intends to analyze the relation between circulation weather patterns, air mass recirculation and pollution levels in three coastal airsheds of Portugal (Lisbon, Porto and Sines) based on the application of an objective quantitative measure of potential recirculation. Although ventilation events have a dominant presence throughout the studied 9-yrs period on all the three airsheds, recirculation and stagnation conditions occur frequently. The association between NO2, SO2 and O3 levels and recirculation potential is evident during summer months. Under high average recirculation potential and high variability, NO2 and SO2 levels are higher for the three airsheds, whilst for O3 each airshed responds differently. This indicates a high heterogeneity among the three airsheds in (1) the type of emission – traffic or industry – prevailing for each contaminant, and (2) the response to the various circulation weather patterns and recirculation situations. Irrespectively of that, the proposed methodology, based on iterative K-means clustering, allows to identify which prevailing patterns are associated with high recirculation potential, having the advantage of being applicable to any geographical location. Highlights: Association between circulation weather patterns, air recirculation and pollution. K-means clustering associates the recirculation potential to circulation patterns. Ventilation events dominate but recirculation and stagnation occurs frequently. High NO2, SO2 and O3 levels events varies substantially among the airsheds. Methodology can be adapted to other geographical areas.